Does policy uncertainty travel across borders? Evidence from MNC subsidiary investment decisions - Zhou, Xi; Xiao, Min; Wu, Huiying; You, Jiaxing (Journal of Banking & Finance, 2024)
Using a large-scale proprietary data set from China, we examine the cross-border transmission of policy uncertainty within multinational corporations (MNCs). Our results show that policy uncertainty in MNCs’ home countries negatively affects the capital investment of their foreign subsidiaries. Our analyses of cross-sectional heterogeneity reveal that the effect is strengthened by subsidiary-level investment irreversibility and the dependence of subsidiaries on parent firms, and weakened by bilateral meetings and psychic closeness between the home and host countries. Together these findings suggest that policy uncertainty travels across borders and has a spillover effect on foreign subsidiary investment.